URINE PROTEIN PICTURE IN PREGNANT WOMEN WITH HIPERTENS STATUS IN TASIKMALAYA CITY HOSPITAL - Ferdiani, Dina - (LP2M IIK (Lembaga Penelitian dan Pengabdian Masyarakat Institut Ilmu Kesehatan) Bhakti Wiy, 2025)
Preeclampsia is a pregnancy complication that usually occurs after the 20th week of pregnancy. Preeclampsia is caused by an inflammatory reaction. It is characterized by high blood pressure (hypertension) and high protein in the urine (proteinuria). The purpose of this study was to determine the picture of urine protein in pregnant women with preeclampsia at Tasikmalaya City Hospital. The benefits of this study are to increase insight and knowledge about the picture of urine protein in pregnant women with preeclampsia. This study uses a research method or descriptive method using a purposive sampling blood sampling technique. The results of the study were analyzed using frequency distribution and average. The results of the study from 20 pregnant women (100%) showed that 10 people (50%) had urine protein levels (1+), 7 people (35%) had urine protein levels (2+), 3 people (15%) had urine protein levels (3+), in the third trimester of pregnancy there were 9 pregnant women, in the second trimester there were 3 pregnant women, and in the third trimester there were 4 pregnant women. The conclusion of this study is that the picture of urine protein results can be a predictive factor for preeclampsia.